Discovery of potential alleles for iron (Fe) toxicity tolerance in rice: Phenotypic and genotypes analysis of doubled haploid lines (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Chrisnawati L, Miftahudin, Utami DW. 2025. Discovery of potential alleles for iron (Fe) toxicity tolerance in rice: Phenotypic and genotypes analysis of doubled haploid lines. Biodiversitas 26: 851-858. Tidal swamplands present a promising opportunity for expanding rice cultivation. However, iron (Fe) toxicity poses major obstacles to development. To overcome these challenges, it is crucial to develop Fe-tolerant rice genotypes and identify molecular markers, such as single nucleotide polymorphisms (SNPs). This study aimed to identify Fe-tolerant doubled haploid rice genotypes and SNP markers related to Fe toxicity tolerance. The experiment was carried out by cultivating 45 doubled haploid rice lines (BMIP 1-BMIP 33 and BMIP 39-BMIP 50), derived from reciprocal crosses between IR54/Parekaligora and Bio 110/Markuti, under Fe-toxic conditions. Phenotypic evaluations were based on the leaf bronzing symptom (LBS) score and genotype analysis was performed using high-throughput sequencing of 384 SNPs. SNPs correlated with phenotypic data were analyzed using the Tassel 2.0 software, with significance set at a p-value
Keywords: Doubled haploid rice, Fe tolerant, genomic, leaf bronzing symptom, single nucleotide polymorphisms